VERBAL MEANS REALISING THE SPEECH PRODUCED BY CHARISMATIC AMERICAN POLITICIANS OF DIFFERENT PSYCHO-TYPES - Бойченко, Марія (Current Issues of Foreign Philology, 2021)
By analysing the speeches of charismatic American politicians belonging to extraverted and introverted psycho-types, the author came up with the inventory of verbal means characterising their public speech. The article highlights the phenomenon of charisma within the framework of its multi-aspect and multidisciplinary nature as well as summarises distinctive qualities of a charismatic political leader. It is has been found out that it is impossible to describe a definite type of a charismatic personality, while the degree of charisma manifestation for a political personality is conditioned by a number of psychophysiological, sociocultural and political factors. Based on the results of summarising theoretical and experimental data on the interrelation between a person’s psychological characteristics and their speech, it is deemed reasonable to consider two communicative behaviour models distinctive for charismatic politicians of introverted and extraverted psychotypes respectively. By analysing the speeches of charismatic American politicians, who belong to extraverted and introverted personality types according to the expert data, it is found out that, on the one hand, the extraverted speech tends to be more emotional, it is characterised by the linguo-stylistic markers of informality and is described as less structured and less logical as opposed to the introvert’s speech. On the other hand, the introverts structure their utterances more logically abiding by the linguostylistic norms of communication. The distinctive features of the extraverted politicians’ speech comprise the deviations from syntactic and lexical norms and an ample use of the conversational vocabulary; while the speech of an introverted politician is characterised by the variety of elaborated syntactic constructions and rich vocabulary. The study revealed that the actualisation of the charismatic politician verbal speech is conditioned by the form of a political discourse that can modify the distinctive linguostylistic manifestation of a political personality being of an extraverted or introverted type.